1989
DOI: 10.1002/etc.5620080106
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Activity for uptake and toxicity of DDT‐type insecticides utilizing an NMR method for estimating σ*

Abstract: Structure‐activity relationships were examined in toxicological studies with DDT‐type insecticides. The Taft σ* parameter for the electronegative character of substituents correlated well with the uptake of the analogs through insect tarsi and with acute oral toxicities to mice. Substituent groups with stronger electron‐withdrawing capacities penetrated more slowly through the insect cuticle and were markedly more toxic to mice. A nuclear magnetic resonance method was utilized to obtain estimated σ* values for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The situation for insecticides is more complex than for herbicides because of the interactions between the plant and the insect. For contact activity, insecticides must be absorbed through the insect integument; however, insecticides may be taken up by the plant which is eaten by the insect, in which case the compound may be absorbed into the insect through the midgut 46–49. No attempt has been made in this study to distinguish between insecticides that act primarily through contact activity and primarily as stomach poisons.…”
Section: Introductionmentioning
confidence: 99%
“…The situation for insecticides is more complex than for herbicides because of the interactions between the plant and the insect. For contact activity, insecticides must be absorbed through the insect integument; however, insecticides may be taken up by the plant which is eaten by the insect, in which case the compound may be absorbed into the insect through the midgut 46–49. No attempt has been made in this study to distinguish between insecticides that act primarily through contact activity and primarily as stomach poisons.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrate the importance ofthe aliphatic moiety electronegativity in mammalian toxicity QSAR as well with an optimum a apparent at 1.5-2.5 (14).…”
Section: Ddt-type Insecticidesmentioning
confidence: 83%
“…We hypothesised that rising minimum temperatures and better water circulation at higher latitudes and mid-altitudes (Gao, Pan, & Zhang, 1991), caused by climate change, will allow S. mukorossi to expand into these areas. Clark (Clark & D., 2004) indicated that average temperature and rainfall were generally negatively correlated in the tropics, and de la Peña and Hughes stated (Pea & Hughes, 2007) that climate change will lead to more erratic rainfall patterns and unpredictable high temperature spells in the tropics. In the face of future climate change, extreme heat and erratic rainfall and drought at low latitudes will likely lead to localised areas that are no longer suitable for the distribution of S. mukorossi.…”
Section: Response Of Suitable Habitat Distribution To Future Climate Changementioning
confidence: 99%